2008
DOI: 10.1139/w07-110
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of 7 fluorescent pseudomonad clinical isolates

Abstract: There is some debate about the potential survival of Pseudomonas fluorescens at temperatures above 37 degrees C and its consequences for infectious potential, owing to the heterogeneity of clinical strains. Seven clinical strains growing at 37 degrees C or more were submitted for polyphasic identification; 2 were identified as Pseudomonas mosselii and 4 were precisely characterized as P. fluorescens bv. I or II. The binding indexes on glial cells of the strains identified as P. fluorescens bv. I and P. mosseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 26 publications
4
61
0
Order By: Relevance
“…3). Isolates of P. fluorescens derived from nonmammalian samples have a permissive growth range of 4 to 32°C (62), while isolates from humans and other mammals have an elevated upper range extending to 37°C (53,(57)(58)(59). As of the end of 2013, there were 16 fully sequenced strains from the P. fluorescens species complex, and all but one originated from plant surfaces, roots, or the surrounding soil (Table 4).…”
Section: Phenotypic Traits and Cultivation Of P Fluorescensmentioning
confidence: 99%
See 3 more Smart Citations
“…3). Isolates of P. fluorescens derived from nonmammalian samples have a permissive growth range of 4 to 32°C (62), while isolates from humans and other mammals have an elevated upper range extending to 37°C (53,(57)(58)(59). As of the end of 2013, there were 16 fully sequenced strains from the P. fluorescens species complex, and all but one originated from plant surfaces, roots, or the surrounding soil (Table 4).…”
Section: Phenotypic Traits and Cultivation Of P Fluorescensmentioning
confidence: 99%
“…For example, we have a collection of over 30 P. fluorescens strains from cystic fibrosis patients that grow well at 37°C. Another study reported a series of P. fluorescens isolates from surface abscess, septicemia, and respiratory or urinary tract infections that were able to grow at 37°C (57). All seven were also able to grow at 4°C, often considered the lower limit of the optimal temperature range of Pseudomonas spp.…”
Section: Phenotypic Traits and Cultivation Of P Fluorescensmentioning
confidence: 99%
See 2 more Smart Citations
“…P. fluorescens was isolated in bottled water and causing bacteremia and pseudo bacteremia in immunocompromised patients in hospitals from contamination of disinfectants and blood collecting tubes [22]. Although P. fluorescens considered to be non-pathogenic to humans, but recent reports on clinical strains of P. fluorescens have cause serious health problems [23][24][25] which require some alternative treatment approach.…”
Section: Discussionmentioning
confidence: 99%